First Prize for Ayia Napa Competition for Consultation Services for Designing and Supervising of the Upgrade Project of Parks: “Sculpture Park” - Antoniou, Klitsa (My University, 2026)
First Prize for Ayia Napa Competition for Consultation Services for Designing and Supervising of the Upgrade Project of Parks: “Sculpture Park”, “Park of Mediterranean Plants, Cactus and Succis’’ and “Cave of Palaeontological Discoveries”. Member of the Polytia armos Architects Team.
Keywords: Arts and entertainment